Regional economic security: the essence of the concept and boundaries of application - T Y Feofilova (RUDN Journal of Economics, 2010)
The article raised questions about the appropriateness of the term «regional economic security». It is proposed an analytical review of the definition of «region» in the normative legal space of Russia and in scientific research. Objects and levels of economic security were refined. Justify the inclusion of multiple levels of the economic security of the country meso-level of the combined economies of the RF subjects. Proposed by regional economic security to consider two levels: the level of economic security of federal entities and meso-level of economic security.